Studentsâ Ability and Difficulties in Understanding English Text (A Study at English Program IAIN Padangsidimpuan) - Harida, Eka Sustri (AT-TALIM, 2014)
This study deals with the ability of the students to understand English texts and types of their reading strategies. It is believed that reading strategies help students improve their reading comperehension.Â  Based on this theory, then, the qualitative research was carried out to describe studentsâ reading ability and types of strategy they used. Data were collected through questionnaires that have been distributed to 34 students.Â  They were also observed and tested.Â  It was found that the studentsâ ability in understanding text was still low. They had many problems in understanding English texts because they did not apply appropriate reading strategies in their reading activities. Their low reading comprehension was due to their lack of reading strategies.Â Copyright Â© 2014 by Al-Talim All right reserved